On-chip electromembrane extraction followed by sensitive digital image-based colorimetry for determination of trace amounts of Cr(vi). Issue 4 (23rd December 2019) - Zarghampour, Fereshteh; Yamini, Yadollah; Baharfar, Mahroo; Javadian, Ghazal; Faraji, Mohammad
Abstract : In this work, an on-chip electromembrane extraction coupled with the micro solid phase extraction step was developed for extraction, preconcentration, and determination of trace amounts of chromium(vi ) in water samples. Abstract : In this work, an on-chip electromembrane extraction coupled with the micro solid phase extraction step was developed for extraction, preconcentration, and determination of trace amounts of chromium(vi ) in water samples. The method is based on the selective complexation of chromium(vi ) with 1, 5-diphenylcarbazide followed by extraction and preconcentration in an acceptor phase via the application of an electrical field. For further preconcentration and digital image analysis, the device was coupled to a micro-packed column. After the adsorption of the complex on the sorbent, an intense violet color appeared which was directly analyzed by RGB colorimetry using a smart phone. For carrying out the analysis via a smart phone, an integrated device was required. For this goal, a microfluidic chip consisting of two platforms with spiral channels and embedded electrodes was exploited. The spiral design of the channels was expected to increase the contact surface between the sample solution and extraction phase and prevent the acceptor phase from early saturation. In addition, packing the sorbent can provide acceptable preconcentration and remarkable sensitivity for analysis of digital image components. Considering optimal conditions, the chromium complex was extracted from aqueous sample solutions into 500 μL of an acidified (HCl 100 mM) acceptor solution. The polypropylene membrane was impregnated with 2-nitrophenyl octyl ether containing 15% di-(2-ethylhexyl) phosphate (DEHP), and a relatively low voltage value of 30 V was applied over the supported liquid membrane. Under optimal conditions, a limit of detection down to 10 μg L −1 was obtained by smart phone detection. The calibration curve was linear in the range of 30–1000 μg L −1 with a correlation coefficient of 0.9969. The inter- and intra-assay RSD% values were lower than 7.6%.